Climate Change in the Peruvian Andes: A Case Study on Small-Scale Farmers’ Vulnerability in the Quillcay River Basin - Anna Heikkinen (Iberoamericana: Nordic Journal of Latin American and Caribbean Studies, 2017)
Previous studies have shown that climatic changes in the Peruvian Andes pose a threat to lowland communities, mainly through changes in hydrology. This study uses a case study approach and a mixed qualitative-quantitative method to examine the vulnerability of small-scale farmers in the Quillcay River basin to variations in precipitation and enhanced glacier retreat. The findings of the study show partly contradicting results. On one hand, interpretation of semi-structured interviews suggests a strong relation between climate proxies and increased vulnerability of the smallholders. On the other hand, in the quantitative analysis enhanced glacier retreat seemed to have augmented vulnerability solely to some extent whereas precipitation did not show significant impact. The assessment of the socioeconomic dimension revealed that larger market forces, weak political entitlement and lack of social and economic capital fundamentally increased smallholders’ vulnerability. It is, therefore, suggested that a complex cluster of economic, political and social factors are the root causes of small-scale farmers’ vulnerability in the case study region whereas climate-related changes merely act as multiplying factors.